The Restoration of Hope and Dignity in the Context of the Sexual Abuse Crisis in the Church - Peter De Mey (Communio Viatorum)
This article looks at the sexual abuse crises that have hit churches around the world, especially the Roman Catholic Church, and asks if it is possible to talk of hope in such circumstances. It asks whether theology has a role to play or a responsibility for the crisis, and what sort of church is called for in the light of it. The article ends by suggesting possible places of hope that do not seek to impose on the survivors.